Prawda, przebaczenie i pojednanie jako ważne aspekty procesu zdrowienia człowieka w wybranych obrazach filmowych = The truth, forgiveness and reconciliation as important aspects of a person`s healing process in selected scenes from movies - Fromont, Karol (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is a reflection on widely understood health based on chosen movie clips. Thus, health is understood as an entire well-being, namely physical, mental, spiritual and relational, of a human being. The author presents how those three aspects that lead to healing and health, namely: truth, forgiveness and reconciliation, are portrayed in films that are seen here as means to describe human experiences. Presented and described scenes from chosen movies portray an ample array of internal struggles of main characters as well as complicated relationships that may or may not lead to recovery. Those three aspects: truth, forgiveness and reconciliation are presented as significant elements of recovery in relationship with oneself, others and God.
Keywords: prawda; przebaczenie; pojednanie; zdrowie; film; truth; forgiveness; reconciliation; health